A Brief Review of Current Maturation Methods for Human Induced Pluripotent Stem Cells-Derived Cardiomyocytes - Ahmed, Razan Elfadil; Anzai, Tatsuya; Chanthra, Nawin; Uosaki, Hideki (Frontiers in Cell and Developmental Biology, 2020)
Cardiovascular diseases are the leading cause of death worldwide. Therefore, the discovery of induced pluripotent stem cells (iPSCs) and the subsequent generation of induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) was a pivotal point in regenerative medicine and cardiovascular research. They constituted an appealing tool for replacing dead and dysfunctional cardiac tissue, screening cardiac drugs and toxins, and studying inherited cardiac diseases. The problem is that these cells remain largely immature and in order to utilize them, they must reach a functional degree of maturity. To attempt to mimic in vivo environment, various methods including prolonging culture time, co-culture and modulations of chemical, electrical, mechanical culture conditions have been tried. In addition to that, changing the topology of the culture made huge progress with the introduction of the 3D culture that closely resembles the in vivo cardiac topology and overcomes many of the limitations of the conventionally-used 2D models. Nonetheless, 3D culture alone is not enough, and using a combination of these methods is being explored. In this review, we summarize the main differences between immature, fetal-like hiPSC-CMs and adult cardiomyocytes, then glance at the current approaches used to promote hiPSC-CMs maturation. In the second part, we focus on the evolving 3D culture model—it’s structure, the effect on hiPSC-CMs maturation, incorporation with different maturation methods, limitations and future prospects.